2001
DOI: 10.1007/s002640100263
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification following internal fixation or arthroplasty for displaced femoral neck fractures: a prospective randomized study

Abstract: One hundred hips in 99 patients of 75 years or older, with a displaced femoral neck fracture, were studied for heterotopic ossification (HO). The patients were randomized to either internal fixation or total hip arthroplasty (THA). In the THA group HO was found in 32 of 45 hips compared with 1 of 39 in the internal fixation group (P<0.0012). The frequency of HO after THA corresponds well with findings in other studies on patients receiving THA for osteoarthrosis. In cervical fractures the surgical procedure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…U sing prospectively collected data from the HEALTH trial, we investigated the prevalence of HO following arthroplasty for hip fractures as well as the risk of revision surgery and the functional outcomes associated with this condition. Our findings confirm that the development of HO following THA or HA for a femoral neck fracture is fairly common, although the prevalence of 19.9% for any grade of HO at 24 months postoperatively in our study is lower than that in previous reports, in which the prevalence has usually ranged from 27.9% to 86.9% [27][28][29][30][31][32][33][34][35][36][37][38] . The prevalence of severe HO (grade III or IV) was 4.4% (63 of 1,441) in our study, in which only 5 patients (0.35%) had hip ankylosis (grade IV), which is similar to the previously reported prevalence of 3.6% to 7% for grades-III and IV HO following THA or HA 3,[39][40][41] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…U sing prospectively collected data from the HEALTH trial, we investigated the prevalence of HO following arthroplasty for hip fractures as well as the risk of revision surgery and the functional outcomes associated with this condition. Our findings confirm that the development of HO following THA or HA for a femoral neck fracture is fairly common, although the prevalence of 19.9% for any grade of HO at 24 months postoperatively in our study is lower than that in previous reports, in which the prevalence has usually ranged from 27.9% to 86.9% [27][28][29][30][31][32][33][34][35][36][37][38] . The prevalence of severe HO (grade III or IV) was 4.4% (63 of 1,441) in our study, in which only 5 patients (0.35%) had hip ankylosis (grade IV), which is similar to the previously reported prevalence of 3.6% to 7% for grades-III and IV HO following THA or HA 3,[39][40][41] .…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, there are considerable conflicting data regarding the clinical relevance of Brooker grade-III or IV HO. Several authors have found reduced walking ability, function, and range of motion (especially flexion) 5,20,33,38,44,45 in patients with grade-III or IV HO, without an effect on pain scores 5,8,20,33,38 . A meta-analysis by Neal 5 showed Brooker grade-III and IV HO to have a negative correlation with range of motion and functional outcomes, whereas some authors concluded that only very severe HO (Brooker grade IV) is clinically relevant 6,7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concerning this cohort of patients have presented results for only up to two years postoperatively in four papers as well as in a dissertation 4,12,15,16 . The aim of the present study was to evaluate long-term results from a previous study comparing internal fixation and total hip replacement.…”
mentioning
confidence: 97%
“…[7][8][9][10][11][12] Pathologic ossifications are also reported after total hip arthroplasty, anterior cruciate ligament reconstruction, and hip fracture. [13][14][15] There are very few reports about clinical and radiologic aspects of the ossification of STL. 4,5 Haller et al 16 suggested association between ossification of pelvic ligaments and spinal diffuse idiopathic skeletal hyperostosis.…”
Section: Discussionmentioning
confidence: 99%